Design and Implementation of Cultural Portal and Promotion through Social Networks - Thakur, Vijay Singh (My University, 2011)
Thesis presents how we can promote cultural portal using Social networks. This thesis also throws some light over Social computing.Thesis presents statistical data related to social computing paradigms. Thesis shows Example of how Social-Plug-ins can be used to integrate the portal with Social networks like facebook.
M.E. (Software Engineering)
Keywords: Information Sharing; Web 2.0; Cultural computing; Social Networks